Growth intentions in family-based new venture teams: The role of the nascent entrepreneur's R&D behavior. Issue 6 (8th May 2019) - Muñoz-Bullón, Fernando; Sanchez-Bueno, Maria J.; Nordqvist, Mattias
Abstract : Purpose: The purpose of this paper is to investigate how family ties in new venture teams (NVTs) influence the intended future growth of a nascent entrepreneur's business. The authors posit that R&D-oriented entrepreneurs in NVTs with family ties have higher growth intentions relative to those who are less oriented toward R&D. Design/methodology/approach: The hypotheses were tested using data from the Panel Study of Entrepreneurial Dynamics II (PSED II). One distinctive feature of the PSED is that it is based on a random sample of 1, 214 nascent entrepreneurs in the process of starting new ventures in the USA, which overcomes the recall biases associated with surveying entrepreneurs already in business and potential survivorship biases. Findings: The results show that growth intentions in NVTs with family ties is greater when the nascent entrepreneur shows an R&D behavior, even though the presence of family members in the team is negatively related to the intentions of nascent entrepreneurs with regard to new venture growth. This effect is attributed to entrepreneurs' long-term vision and a more favorable attitude toward change. Research limitations/implications: Data on startup teams in the PSED II come from one team member (the respondent). Therefore, differences in perceptions regarding growth intentions cannot be determined. Moreover, the sample consisted exclusively of nascent entrepreneurs in the USA. Practical implications: Knowledge about the determinants of growth intentions during the venture creation phase becomes relevant if we want to influence and support the growth of newly founded firms. Nascent entrepreneurs need to understand the trade-off between emotional and financial concerns. Social implications: Nascent entrepreneurs more oriented toward R&D become more risk tolerant, and may accept certain losses to their emotional endowment in favor of pure financial goals, being more able to access the additional external resources (tangible and intangible) needed for growth. Originality/value: The research expands previous evidence on the family involvement-performance debate in large firms by focusing on new ventures with family ties, with distinctive characteristics that may affect growth intentions. The authors also shed new light on the interplay between family business and entrepreneurship. In particular, the research helps gain an understanding of how NVTs with family ties deal with the opposition between the benefits from venture growth and the tendency to preserve team member's emotional attachment.